2017
DOI: 10.1038/nn.4533
|View full text |Cite
|
Sign up to set email alerts
|

Capillary K+-sensing initiates retrograde hyperpolarization to increase local cerebral blood flow

Abstract: Blood flow into the brain is dynamically regulated to satisfy the changing metabolic requirements of neurons, but how this is accomplished has remained unclear. Here, we demonstrate a central role for capillary endothelial cells in sensing neural activity and communicating it to upstream arterioles in the form of an electrical vasodilatory signal. We further demonstrate that this signal is initiated by extracellular potassium (K+)—a byproduct of neural activity—which activates capillary endothelial cell inward… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

34
565
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 391 publications
(627 citation statements)
references
References 50 publications
(78 reference statements)
34
565
2
Order By: Relevance
“…Yet the observed spatial scale nominally corresponds to the ~2 mm electrotonic length along the endothelial cells that form the lumen of the vessel (Segal and Duling, 1989). We thus surmise that intrahemispheric coherence within the arteriole network is in part mediated by signaling along endothelial cells that form the lumen (Longden et al, 2017), in addition to neuronal interactions. This view is supported by disruption of the front of vasodilation by precise light-induced disruption of conducted dilation within the arteriole network (Chen et al, 2014).…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Yet the observed spatial scale nominally corresponds to the ~2 mm electrotonic length along the endothelial cells that form the lumen of the vessel (Segal and Duling, 1989). We thus surmise that intrahemispheric coherence within the arteriole network is in part mediated by signaling along endothelial cells that form the lumen (Longden et al, 2017), in addition to neuronal interactions. This view is supported by disruption of the front of vasodilation by precise light-induced disruption of conducted dilation within the arteriole network (Chen et al, 2014).…”
Section: Discussionmentioning
confidence: 94%
“…A final unknown concerns the precise mechanism by which neurons drive the endothelial cells (Attwell and Iadecola, 2002; Cauli and Hamel, 2010). Likely candidates for prompt signaling to arterioles are prostaglandin release (Lacroix et al, 2015) and bursts of potassium in the perivascular space (Longden et al, 2017). These mechanisms are important on fundamental grounds (Kleinfeld et al, 2011) and as a means to further improve the interpretation of BOLD (Logothetis and Wandell, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…For example, in the auditory, visual and cerebellar cortex the vascular response does not faithfully match the activated area (Harrison et al, 2002; Iadecola et al, 1997; O’Herron et al, 2016), while in the olfactory bulb there is close overlap between the two (Chaigneau et al, 2003). Non-overlapping vascular and neuronal topology in neocortex (Blinder et al, 2013) and retrograde vasodilatation (discussed later in this review) are likely responsible for such lack of fidelity (Chen et al, 2014; Iadecola et al, 1997; Longden et al, 2017). Since hemodynamic signals are the most powerful tool at our disposal for functional brain mapping, their spatial alignment with neural activity is becoming increasingly relevant as the resolution of fMRI increases.…”
Section: Neurovascular Couplingmentioning
confidence: 99%
“…Although much less in know about the mechanisms of retrograde vasodilatation in the cerebral vasculature, a recent study implicates endothelial K IR channels, rather than K Ca , in the mechanisms of the fast component. Enriched with K IR channels, but not K Ca channels, capillary cerebral endothelial cells are highly sensitive to K + generated during neural activity, either from the abutting astrocytic end-feet or diffusion form nearby synapses (Longden et al, 2017). Owing to a unique capillary-parenchymal arteriole preparation, this study showed that micropipette application of 6–10mM K + to capillaries generated a robust hyperpolarization in endothelial cells, transmitted retrogradely to penetrating arterioles at an estimated speed of 2mm/sec, and leading to hyperpolarization and relaxation of SMC (Longden et al, 2017).…”
Section: Neurovascular Couplingmentioning
confidence: 99%
See 1 more Smart Citation